(untitled) (Bangladesh Veterinarian, 2023)
The study was conducted to know the effects of age on haemato-biochemical profiles in Black Bengal (BB) goats. Fifty BB goats were equally divided into five groups: group A (control, 3 years), group B (>3 - 5 years), group C (2-<3 years), group D (1-<2 years) and group E (<1 year). Most of these haemato-biochemical parameters were within the normal range of reference values, except Albumin and ALP. The significantly (P<0.01) higher concentrations of RBC (17.9 ± 0.2 Million/cu mm), WBC (14.4 ± 0.3 Thousands/cu mm), Haemoglobin (9.0 ± 0.2 gm/dl) and PCV (29.9 ± 0.2%) were found in group B. The percentage of Neutrophil (35.2 ± 0.4%), Eosinophil (1.0 ± 0.0%) and Basophil (0.6 ± 0.0%) were higher in group E. Percentage of Lymphocyte (60.0 ± 0.4 %) and Monocyte (3.5 ± 0.2%) was higher in group B than other younger groups. The significantly (P<0.05 and P<0.01) higher concentration of total protein (74.7 ± 0.2g/L) and globulin (46.3 ± 0.5 g/L) respectively, were in Group B. Albumin (28.4 ± 0.2g/L) and ALT (22.3 ± 0.5 U/L) concentrations were significantly P<0.02) higher in Group E than other groups of goat. Bangl. vet. 2022. Vol. 39, No. 1-2, 43–53